The Andromeda strain [videorecording (DVD)] - Hill, Arthur, 1922-2006; Wayne, David, 1914-1995; Olson, James, 1930-; Crichton, Michael, 1942-2008 (Universal Studios, 2003)
A remote village in New Mexico is contaminated by a crashed satellite. Scientists fight the clock trying to analyze the lethal organism and discover a solution.